2015
DOI: 10.1016/j.ejor.2015.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Selective vehicle routing for a mobile blood donation system

Abstract: a b s t r a c tIn this study, a mobile blood collection system is designed with the primary objective of increasing blood collection levels. This design also takes into account operational costs to aim for collection of large amounts of blood at reasonable cost. Bloodmobiles perform direct tours to certain activities to collect blood, but at the end of each day, they bring the collected blood to a designated depot to prevent its spoilage. The proposed system consists of the bloodmobiles and a new vehicle calle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(29 citation statements)
references
References 26 publications
0
29
0
Order By: Relevance
“…Ensafian et al ( 2017 ), Ensafian and Yaghoubi ( 2017 ), Osorio et al ( 2017 ), Hosseinifard and Abbasi ( 2018 ), Clay et al ( 2018 ), Hosseinifard et al ( 2020 ) can be shown as recent examples. In addition, Ghandforoush and Sen ( 2010 ), Şahinyazan et al ( 2015 ), Blake et al ( 2015 ), Gunpinar and Centeno ( 2016 ), Elalouf et al ( 2018 ) focus on the logistics of blood products in the supply chain. The status of the blood supply chain network design and optimization after any disaster and emergency situations is also a sub-area.…”
Section: Literature Surveymentioning
confidence: 99%
See 1 more Smart Citation
“…Ensafian et al ( 2017 ), Ensafian and Yaghoubi ( 2017 ), Osorio et al ( 2017 ), Hosseinifard and Abbasi ( 2018 ), Clay et al ( 2018 ), Hosseinifard et al ( 2020 ) can be shown as recent examples. In addition, Ghandforoush and Sen ( 2010 ), Şahinyazan et al ( 2015 ), Blake et al ( 2015 ), Gunpinar and Centeno ( 2016 ), Elalouf et al ( 2018 ) focus on the logistics of blood products in the supply chain. The status of the blood supply chain network design and optimization after any disaster and emergency situations is also a sub-area.…”
Section: Literature Surveymentioning
confidence: 99%
“…These two assumptions are commonly made in the literature (i.e., Ensafian and Yaghoubi ( 2017 ), Arvan et al ( 2015 ), Şahinyazan et al ( 2015 ), Jabbarzadeh et al ( 2014 )). Hence, we also resort to homogeneity assumptions.…”
Section: Multi-objective Mixed-integer Mathematical Modelmentioning
confidence: 99%
“…Salehipour and Sepehri [41] dealt with blood distribution management to minimize total waiting time of hospitals and medical centers and tackled a real problem containing 24 hospitals. Şahinyazan et al [40] examined how blood from mobile centers is collected and sent to blood banks. They considered a vehicle for each district to move from a blood bank, collect donated blood from temporary centers, and then return to the same blood bank.…”
Section: Location-allocation Models For Blood Supply Chainmentioning
confidence: 99%
“…deciding the location of both mobile and fixed donation clinics, and often also attempt to minimise the costs involved with moving clinics and transportation of blood products. The next most popular area of research within this category is the planning of clinics, such as the explicit scheduling of clinics at locations that are already assigned [2,45]. Several articles in this category either focus on relocating or establishing a new facility such as a blood centre or stock holding unit [10,16,29,44], whilst the comparison of effectiveness of mobile and fixed clinics is also considered [3].…”
Section: Location/clinic Planningmentioning
confidence: 99%